Proton supplier role of binuclear gold complexes in promoting hydrofunctionalisation of nonactivated alkenes - Asgari, Maryam; Hashmi, A. Stephen K. (Catalysis science & technology, 2019)
Density functional theory (DFT) was used to investigate PR3AuOTf-catalyzed hydrofunctionalisation of nonactivated alkenes using acetic acid and phenol where OTf = triflate (CF3SO3−). The gold(I) complex itself is found to be unlikely to operate as the π-activator due to its relatively low electrophilicity. Instead, the concurrent coordination of two gold(I) complexes to a nucleophile (PhOH or AcOH) enhances the acidity of the latter's proton and causes the ensuing binuclear complex to serve as a strong proton supplier for activating the alkene π-bonds. Alternatively, the binuclear complex is also susceptible to produce a hidden HOTf. This hidden acid is accessible for hydrofunctionalization to occur but it is not in sufficient concentration to decompose the final product.